Evaluating Tsunami Memorial Museums in Indonesia and Japan as Post-Disaster Dark Tourism Sites - Cahyanti, Mega Mirasaputri (International Journal of Disaster Management, 2024)
The 2011 GEJET in Japan and the 2004 IOET in Indonesia led to the development of tsunami memorial museums in these countries. While this type of tourist site is a new phenomenon in Asia, it aligns with the theory of dark tourism, which focuses on death, suffering, and disaster, particularly those caused by humans. This paper explores whether post-disaster memorial museums, caused by natural hazards, can be classified as dark tourism sites. Four key factors examined include attractiveness, exhibition content, attitude of empathy, and educational programs, to assess how these sites align with the principles of dark tourism. Primary data were gathered from eight respondents (museum managers and tour guides) using online surveys and fieldwork observations as data collection techniques. This study employed a qualitative descriptive analysis technique with a comparative case study. The paper shows that ITMM and MTA use tragic events to heighten emotions and empathy to provide an affective educational process, which can be classified as dark tourism sites. The museum has different exhibition approaches, where MTA incorporates Islamic beliefs and spiritual elements, while ITMM uses a secular and scientific approach to evoke strong emotions. A similarity was found where both museums have symbolic memorial spaces where visitors can show respect in silence or prayer. Ethical issues are addressed by prohibiting photography and video recording out of respect for the victims. The study has implications for other countries with frequent natural disasters to develop similar museums as learning sites that promote empathy and disaster awareness.